Socioeconomic inequalities in post-natal health checks for the newborn in Vietnam - Nguyen Duc Lam; Nguyen Duy Anh; Nguyen Thi Thu Ha; Truong Quang Vinh; Vu Thi Mai Anh; Vu Duy Kien (BMC, 2019)
Abstract Background The newborn and child death associated with inadequate post-natal health checks continued to be a significant issue across the world. This study aimed to assess the socioeconomic inequalities in post-natal health checks for the newborn in Vietnam in 2014. Methods We used the secondary data from the Multiple Indicator Cluster Survey in 2014. We included women aged 15-49 years who had a live birth within two years of the time of the interview. We estimated the concentration index to measure socioeconomic inequalities post-natal health checks for the newborn. We conducted multiple logistic regression analysis to identify factors associated with post-natal health checks for the newborn. Results Overall, the proportion of post-natal health checks for the newborn in Vietnam was 89.1%. The concentration index of post-natal health checks for the newborn was positive at 0.06. It indicated that the newborns in the rich households were more likely to get post-natal health checks as compared to in the poor households. The common factors significantly associated with the higher percentage of post-natal health checks for the newborn were women belonging to the Kinh and Hoa ethnic, higher education, and wealthier groups. Conclusion Socioeconomic inequalities in post-natal health checks for the newborn in Vietnam were not strong, but it still existed. Thus, we recommended that policy efforts to increase access to post-natal health services for poor women. In addition, there is a need to improve access to post-natal health services for women belonging to minor ethnic group and low education.